Capital Account Liberalization and External Debt - Zehri, Chokri (International Journal Of Management And Economics Invention, 2017)
This paper examines the impact of capital account liberalization on the external debt of South Mediterranean Countries (SMCs). We use 5 models to explain the growth of external debt by macroeconomics variables and especially by variables reflecting the capital liberalization. Using panel data for 8 countries from 1971 to 2015, we find that capital account liberalization is negatively correlated with external debt. We also find that the macroeconomic instability has an important role in the rise of external debt. JEL Classification Numbers: F30; F36; F38; F41.